PERCEPTION OF PALLIATIVE CARE OF HEALTH PROFESSIONALS IN THE HOSPITAL ENVIRONMENT OF THE MUNICIPALITY OF PINHEIRO-MA - Santos, Raissa da Silva (2021)
Introduction: Palliative care has brought changes in the practice of professionals in health services, by adding the role of caring for the process of dying. However, it is a fact that, in health degrees, an approach to this topic is still insufficient and this has directives on the type of care offered to patients with limiting and life-threatening conditions Objective: to assess the perception of health professionals about Care Palliative. Materials and method: Exploratory study with a qualitative approach carried out with health professionals from the hospital network in the city of Pinheiro, Maranhão. Eighteen professionals participated in the research, of which 12 nurses and 6 doctors. Data collection took place through semi-structured interviews, with the statements recorded and later transcribed to allow the interpretation of the data that followed the method of thematic analysis in Bardin. Results: Professionals with little knowledge about the topic, besides insecurity to deal with terminality and the guarantee of patient autonomy. In addition, there was a difficulty in accepting death both on the part of the team and on the part of the patient and family. Conclusion: The appropriation of the knowledge of Palliative Care is essential for the guarantee of human dignity. Therefore, the provision of training and the discussion of this topic in the work environment is essential to guarantee the individual's quality of life.